EBA Knowledge Repository - German, Maria Isabel I.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2010)
Equation Branch Automation (EBA) is part of Misys-Equation Banking System designed to support customer-facing staff within a retail branch banking environment. The EBA system is tightly integrated with the Equation core system, and provides ready-to-run functionality to support cashiers, personal bankers and relationship managers. EBA allows online, real-time transaction processing with immediate access to account and transaction information and verification of availability of funds. As part of Misys' services, the company aims to continue satisfy its clients' needs through its Customer Support Services. Thus the project proposed a new process of preserving knowledge that is gained through the years by the employees focusing on the EBA team. EBA Knowledge Repository facilitates the set up of a centralized and accessible repository of training materials for new joiners, compilation of lessons learned, best practices and other training references acquired through time. The project aims to promote effective knowledge transfer to employees that can be used for their advantage and of the company. Surveys were conducted among the EBA team members and immediate manager to assess the success/failure of the project. With the continuous growth of customers and support demands, one must agree that most of corporate knowledge is in people rather than in physical or financial assets and this have become important in the knowledge economy. One inevitable scenario in every organization is that "knowledge" are lost when the employees leave or are regrouped. With this project if proven successful, would be used and utilized in other teams and groups.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Knowledge management